2021
DOI: 10.1177/15589447211003184
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence Rates of Dorsal Wrist Ganglion Cysts After Arthroscopic Versus Open Surgical Excision: A Retrospective Comparison

Abstract: Background This study directly compares the recurrence rates of dorsal wrist ganglion cysts in patients treated via open surgical excision versus arthroscopic surgical excision. We hypothesized that there would be no difference between recurrence rates with these 2 surgical options. Methods We retrospectively reviewed the charts of all patients with a dorsal ganglion cyst undergoing either open or arthroscopic surgical excision at a single academic center with 3 fellowship-trained attending hand surgeons from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
3
0
1
Order By: Relevance
“…Splinting to allow soft-tissue rest is frequently used for 1 to 2 weeks after surgery, although there is no clear evidence that splinting improves outcomes after cyst excision. 24 Recurrence rates after open excision range between 7% and 39% 21,25,26 in recent series.…”
Section: Dorsal Wrist Ganglion Cystsmentioning
confidence: 99%
“…Splinting to allow soft-tissue rest is frequently used for 1 to 2 weeks after surgery, although there is no clear evidence that splinting improves outcomes after cyst excision. 24 Recurrence rates after open excision range between 7% and 39% 21,25,26 in recent series.…”
Section: Dorsal Wrist Ganglion Cystsmentioning
confidence: 99%
“…Dua dari 9 (22%) kekambuhan setelah eksisi ganglion artroskopi dan didapatkan 2 dari 8 (25%) kekambuhan setelah eksisi ganglion terbuka yang menjalani intervensi bedah berulang. Sehingga dalam studi ini menunjukan, eksisi terbuka menyebabkan tingkat kekambuhan yang relatif lebih rendah dibandingkan dengan eksisi artroskopi 12 .…”
Section: Prognosisunclassified
“…3 Recurrence is the most frequently reported complication of any form of treatment and may result from inadequate excision of the stalk of the ganglion. [4][5][6][7] Although traditional ganglion excision in an open approach is considered the gold standard and has yielded satisfactory outcomes with pain relief and functional improvement according to previous studies, 8,9 a high postoperative recurrence rate of approximately 40% was still reported. 10 Therefore, recurrent DWG cysts may frequently be encountered in clinical practice, and the treatment decision and benefit of re-excision should be evaluated with caution.…”
Section: Introductionmentioning
confidence: 99%